Consumer’s Willingness to Pay for Wedding Decoration Analysis during COVID-19 (The Indonesian Journal of Business Administration, 2020)
ARTYS Wedding Designer is a vendor involved in the wedding business, especially in wedding decoration. But with the lockdown in effect due to COVID-19 pandemic, the wedding industry has been brought down to a halt. Since the start of the lockdown in April, ARTYS has mostly stopped operation, with the assets (decoration, etc) stored in the owner’s storage and the freelance employees out of contracts. However with the assumption that wedding decoration demand will recover after COVID, ARTYS is interested in exploring ways to continue business during COVID and also come out ahead of the competition once the lockdown is lifted and wedding ceremonies become the norm again. The research is conducted using two analyses: qualitative and quantitative analyses. For qualitative methods exploratory research of in-depth interviews methods was used to respondents who got married and are planning to get married during the pandemic. For quantitative analysis, online questionnaires was given to 123 random respondents, the respondents were then filtered it into 30 valid respondents who meet the criteria. Using questionnaire multiple regression analysis and Van Westendorp price sensitivity analysis, the end product is the willingness to pay of the consumer during COVID-19.The findings from this research can be used as recommendations for ARTYS based on the consumer’s willingness to pay during COVID-19. Keywords: Wedding Industry, Marketing Research, Willingness to Pay, Multiple Linear RegressionAnalysis, Van Westendorp Price Sensitivity Analysis